Comparison of spermatheca morphology between reproductive and non-reproductive females in social wasps - Hashim, Rosli; Ito, F.; Gotoh, A.; Billen, J. (2008)
Social wasps show an obvious evolution of the differentiation in behavior and external size between reproductive and non-reproductive females, with no clear differences in the Stenogastrinae, via overlap in the Polistinae, to clear differences in the Vespinae. In this study, we examined the morphological appearance of the spermatheca in representative species of these three subfamilies. The general anatomical organization of the spermatheca comprises a reservoir, a duct and two spermathecal glands, and is in line with its common structure in other social Hymenoptera. All examined wasp species have a spermathecal reservoir with uniform wall thickness, which is similar to the situation in the bees, but differentiates them from the ants. Within the wasps, the shape of the reservoir, the shape of the spermathecal glands and their attachment site to the spermatheca differs among the Stenogastrinae, Polistinae and Vespinae. The reservoir wall is thick in the Polistinae and Vespinae, while in the Stenogastrinae, it varies from thin in Parischnogaster to thick in Eustenogaster, with an intermediate situation in Liostenogaster. In all examined species, we found no differences in the spermathecal development between reproductive and non-reproductive wasps. (c) 2007 Elsevier Ltd. All rights reserved.